Digital dental photography: Indispensable part of periodontal practice - Thakor Esha N.; Varghese Jothi M. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2022)
Introduction: Photographs are fundamental in interacting with patients. Defects that are not readily noticeable to the patient will be obvious in still pictures. Thus, dental photography permits the patient to visualize their oral condition and smile with the same perception as the dentist. The use of dental photography is for documentation and many more other purposes like social media or marketing. Conclusion: The use of proper devices and additional accessories enhances the outcome of dental photography. This informative article gives the overview of importance of documentation, use of digital cameras and various intraoral accessories which can help the clinician to obtain the best results.